PENGARUHaPENERAPAN MODELvPEMBELAJARANdPROBLEMqBASED LEARNINGrTERHADAPdPEMAHAMANxKONSEPtMATEMATISo PESERTAkDIDIKzKELASiXIiMIPA SMA NEGERI 1 PAINAN - Sara, Yulia Mai (Departemen Matematika, 2023)
Mathematicskconceptual understanding ability is oneloffabilities thattmust be mastered by students. However, students' understanding of mathematical concepts is not optimal yet. The PBL model can be used to enhance students' knowledge of mathematical concepts. Thekgoal of this researchk is to find out whetherdmathematics conceptual understandingf ability of studentspwho learn with PBL modell is betterk thanq mathematics conceptual understanding ability of students that learning by directj learning. According to the study's findings, it was discovered that the ability of students who studied with PBL was better than those who applied the direct learning model. Keywords – Mathematics Conceptual Understanding, PBL , Direct Learning